Rick Rudy, Stan Horton, Wiggsy Sivertsen - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows from left to right, Rick Rudy, Stan Horton and Wiggsy Sivertsen standing in front of a large High Tech Gays banner with the "HTG" visible. Rudy and Sivertsen are wearing "No on 64" buttons and Sivertsen is also wearing a "Rose Bird yes" button. Stanley Horton was the Assistant Police Chief for San Jose. This photograph may have been taken when Stan Horton apologized at a High Tech Gay meeting for a disparaging remark he allegedly made against gays in 1986.